Analysis of Factors Influencing Switching Intention to Use of M-Payment Applications - Abdurrahim, Teddra Naufal; Aribowo, Agus (Manunggal Halim Jaya, 2026)
Every consumption activity is influenced by various factors related to security, trust, and transaction efficiency. This underpins the importance of adapting to technological innovation, particularly in modern payment systems. The purpose of this study was to evaluate consumer tendencies toward switching to mobile-based digital payment systems (m-payment). The sampling technique used was purposive sampling, with 100 active students from the Faculty of Law and Digital Business, Maranatha Christian University, from 2021 to 2024. The data used was primary data collected through an online questionnaire using Google Forms. This study was analyzed using multiple linear regression using SPSS version 30 software, focusing on the influence of the push effect, pull effect, and mooring effect variables (variable X) on switching intention (variable Y). The results showed that the pull effect and mooring effect had a significant positive influence on the intention to switch to m-payment, while the push effect had a significant negative influence. Of the three variables, the pull effect was the most dominant factor. Although the Push-Pull-Mooring model proved relevant in this study, limitations arose because the study only involved one educational institution, making the results less generalizable. Therefore, it is recommended that future research involve a more diverse sample and consider the addition of new variables.